Mobile Applications for Learning with Children with Autism Spectrum Disorder Based on Augmented Reality: A Brief Bibliometric Analysis: Aplicaciones móviles para el aprendizaje con niños con trastorno del espectro autista basadas en realidad aumentada: un breve análisis bibliométrico - Paico-Campos, Meyluz (2025)
Research on augmented reality-based mobile applications has established itself as a key component for educational and therapeutic innovation in children with Autism Spectrum Disorder (ASD). However, it is important to note that many studies present methodological limitations, such as small sample sizes, heterogeneity in interventions, and technological barriers that hinder their large-scale implementation.